Prediksi Jumlah Pendapatan Daerah Pada Kantor BPKPAD Dengan Metode Fuzzy Time Series - Sry Winda Gultom (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Regional income is an important factor that greatly influences regional finances which is useful as adding value to regional wealth. This research aims to find out what is included in Original Regional Income, what things influence original regional income and how to manage original regional income. This research uses data obtained from the Regional Revenue and Asset Financial Management Agency Office of Humbang Hasundutan Regency. The actual data used in this research is realized income from 2018 to 2020. In this research, the author uses the fuzzy time series method to make predictions. By using this method, the author will carry out a process of predicting or forecasting the amount of income from 2021 to 2023. By using this fuzzy time series method, the calculations carried out by the author produce conclusions with decent forecasting performance, namely in the MAPE value range of 20-50%, namely the error value is 32.86%. With this the absolute error is 11.83 and the prediction accuracy value is 67.17%